Supernatant protein factor, which stimulates the conversion of squalene to lanosterol, is a cytosolic squalene transfer protein and enhances cholesterol biosynthesis - Shibata, Norihito (National Academy of Sciences, 2001)
Squalene epoxidase, a membrane-associated enzyme that converts squalene to squalene 2,3-oxide, plays an important role in the maintenance of cholesterol homeostasis. In 1957, Bloch and colleagues identified a factor from rat liver cytosol termed “supernatant protein factor (SPF),” which promotes the squalene epoxidation catalyzed by rat liver microsomes with oxygen, NADPH, FAD, and phospholipid [Tchen, T. T. & Bloch, K. (1957) J. Biol. Chem. 226, 921–930]. Although purification of SPF by 11,000-fold was reported, no information is so far available on the primary structure or biological function of SPF. Here we report the cDNA cloning and expression of SPF from rat and human. The encoded protein of 403 amino acids belongs to a family of cytosolic lipid-binding/transfer proteins such as α-tocopherol transfer protein, cellular retinal binding protein, yeast phosphatidylinositol transfer protein (Sec14p), and squid retinal binding protein. Recombinant SPF produced in Escherichia coli enhances microsomal squalene epoxidase activity and promotes intermembrane transfer of squalene in vitro. SPF mRNA is expressed abundantly in the liver and small intestine, both of which are important sites of cholesterol biosynthesis. SPF is expressed significantly in isolated hepatocytes, but the expression level was markedly decreased after 48 h of in vitro culture. Moreover, SPF was not detectable in most of the cell lines tested, including HepG2 and McARH7777 hepatomas. Transfection of SPF cDNA in McARH7777 significantly stimulated de novo cholesterol biosynthesis. These data suggest that SPF is a cytosolic squalene transfer protein capable of regulating cholesterol biosynthesis.